Implementation of Apriori Algorithm in Determining Tourism Visit Patterns to Bali - Dewa Agung Krishna Arimbawa P; I Nyoman Angga Prabawa; Putu Arya Mertasana (Doctorate Program of Engineering Science, Faculty of Engineering, Udayana University, 2019)
Bali is a tourist destination terknal destinations internationally. Every month there are hundreds of thousands of tourists who visit Bali. With a high tourist visits, stakeholders must prepare all matters related to tourism in Bali. Because problems can occur when a visit in a particular month high but there is no readiness of the parties involved. The purpose of this study is to look for patterns of tourists visiting Bali using Apriori algorithm. Apriori algorithm is one method of Data Mining Based Rule-based Assossiation that can be used to identify patterns of events. Training data used is the visit of foreign tourists to Bali every month from 1982 to 2018. The calculation of Apriori algorithm also tested using an application that is Weka Data Mining. The results obtained are the rules of association which is a pattern of tourists visiting Bali. For example,